2020
DOI: 10.3892/ijmm.2020.4826
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulation of long non‑coding RNA GACAT1 suppresses proliferation and induces apoptosis of NSCLC cells by sponging microRNA‑422a

Abstract: Increasing evidence has demonstrated the important roles of long non-coding (lnc) RNA in non-small cell lung cancer (NSCLC). lncRNA gastric cancer-associated transcript 1 (GACAT1) has been reported to play an oncogenic role in different types of cancer; however, the function of GACAT1 in NSCLC remains unclear. The present study found that GACAT1 was overexpressed in NSCLC tissues and was associated with poor outcomes in patients with NSCLC. Functional experiments revealed that GACAT1 downregulation inhibited p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…LncRNA NKILA suppressed invasion and migration of TSCC cell through inhibiting epithelial‐mesenchymal transition 33 . Recently, Zhong et al 34 showed that GACAT1 was decreased in NSCLC tissues, and knockdown of GACAT1 inhibited cell growth and promoted apoptosis via suppressing miR‐422a. Wang et al 35 indicated that GACAT1 induced breast tumour progression via sponging miR‐875‐3p.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA NKILA suppressed invasion and migration of TSCC cell through inhibiting epithelial‐mesenchymal transition 33 . Recently, Zhong et al 34 showed that GACAT1 was decreased in NSCLC tissues, and knockdown of GACAT1 inhibited cell growth and promoted apoptosis via suppressing miR‐422a. Wang et al 35 indicated that GACAT1 induced breast tumour progression via sponging miR‐875‐3p.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidences suggest that lncRNAs perform core functions in a broad spectrum of biological phenotype in NSCLC. For instance, lncRNAs CCAT1 [21], PART1 [22] and GACAT1 [23] are overexpressed in NSCLC, thus exerting pro-oncogenic actions. Instead, downregulated LINC00476 [24], MEG3 [25] and WT1-AS [26] in NSCLC are certified as anti-carcinogenic lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA gastric cancer−associated transcript 1 (GACAT1) was upregulated in NSCLC tissues and associated with survival. Mechanically, GACAT1 can negatively regulate miR−422a with YY1 transcription factor as a downstream target ( 105 ). Moreover, Circular RNA hsa_circ_0008305 (circPTK2) and transcriptional intermediary factor 1 γ (TIF1γ) were verified considerably downregulated in NSCLC cells undergoing EMT and tumor metastasis induced by TGF-β, indicating circPTK2 as a prospective therapeutic target for advanced NSCLC ( 106 ).…”
Section: Epigenetics In Nsclcmentioning
confidence: 99%